Analysis of Microfinancing in the Development of MSME Customers - Bella, Yolanda Chintya; Dwiaryanti, Risca; Hasanah, Lailatul (Danadyaksa: Post Modern Economy Journal, 2024)
Sharia banks primarily operate in accordance with Islamic law, which is based on concepts of fairness, balance, benefit, and the avoidance of prohibited aspects such as gharor, maisir, and usury. Bank Syariah Indonesia (BSI) is an exemplary sharia-compliant financial organization that offers financing and other services. It operates using sharia-compliant contracts that have been certified by the National Sharia Council. Microfinance has played a vital role in the financial sector since the early 1980s, with the goal of offering financial services to individuals and small and medium-sized enterprises who are economically disadvantaged. The primary focus is on achieving sustainable development by effectively managing and harmonizing the financial, social, environmental, and governance dimensions. The study employs a qualitative methodology to examine the impact of microfinancing on the development of micro, small, and medium enterprises (MSMEs), as well as the various forms of MSME development. The study examines the provision of funding by banks to businesses and self-employed individuals, with a focus on factors such as trust, agreements, duration, and associated risks. Financing has multiple purposes, such as encouraging commerce and economic activities, mitigating unemployment, allowing the movement of products and money, and fostering economic progress. MSMEs have a substantial impact on the Indonesian economy by making considerable contributions to the country's gross domestic product and employment rates.